The Structural Modulation of Amorphous 2D Tungsten Oxide Materials in Magnetron Sputtering. Issue 35 (19th October 2022) - Zhang, Bo; Cicmancova, Veronika; Ludvik, Benes; Slang, Stanislav; Kutalek, Petr; Motola, Martin; Wagner, Tomas
Abstract: 2D oxide materials have gained tremendous attention in the applications. Herein, a synthesis route of 2D WO3 materials via magnetron sputtering is reported. A deposition between 2D monolayers and thin film structure are accomplished according to the temperature of substrate. And 2D monolayers are only formed on a cooled substrate. Ag doping helps to exfoliate 2D WO3 into freestanding monolayers, in which the thickness of 2D monolayer is only ≈3 nm. The ultralarge size of 2D WO3 shows unique features from the traditional 2D material. Resistive switching device and photocatalysis are discussed as examples of application. There is a clear intermediate resistance state in the device with 2D structure. And the failure of resistive switching device is closely related with the 2D structure of WO3 . In the application of photocatalysis, an improved two‐step exfoliation, achieving a stack of WO3 monolayers with a large internal volume, is utilized. The enhancements of photocatalysis are obtained with 2D WO3 after exfoliation. Abstract : 2D monolayers and thin film WO3 are accomplished via magnetron sputtering. 2D monolayers are only formed on a cooled substrate. Resistive switching device and photocatalysis of 2D WO3 are discussed. The failure of resistive switching device is closely related with the 2D structure of WO3 . In photocatalysis, the enhancements of photocatalysis are obtained with 2D WO3 after their exfoliation.